2021
DOI: 10.5267/j.msl.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of customer satisfaction in relationship with service quality, corporate social responsibility, perceived quality and brand loyalty

Abstract: This paper aims to examine empirically the mediation role of customer satisfaction between service quality, customer perceived value, corporate social responsibility, and brand loyalty at Lebanese private universities. A survey was administered with 378 respondents. A judgmental sample of university students were selected. The framework was tested through structural equation modeling (SEM). The findings indicate that service quality and perceived value influence customer satisfaction while satisfaction fully m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 1 publication
5
19
0
1
Order By: Relevance
“…Furthermore, the perceived value perceived by the customer is also able to increase brand trust in the service brand with a coefficient value of 0.239. These findings are in line with research [37,41,52,53], which say that customer trust in telecommunications service brands is positively and significantly related to products value. Then, perceived value also affects brand loyalty with a coefficient of 0.270.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the perceived value perceived by the customer is also able to increase brand trust in the service brand with a coefficient value of 0.239. These findings are in line with research [37,41,52,53], which say that customer trust in telecommunications service brands is positively and significantly related to products value. Then, perceived value also affects brand loyalty with a coefficient of 0.270.…”
Section: Resultssupporting
confidence: 91%
“…Then, in examining the effect of customer satisfaction on brand loyalty, it finds that customer satisfaction can affect brand loyalty by 0.144. The results of this study reinforce the research [16,17,41,45], which indicated that customer satisfaction is an important factor in strengthening customer loyalty to brands. This research also confirms that brand trust can encourage an increase in the loyal attitude of telecommunications service customers, and is in line with research [8,36,52,56], brand trust has a positive and significant effect on brand loyalty.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Service quality of the select Agri was assessed using the SERVQUAL questionnaire, which included 2 x 23 questions/criteria (23 questions for the expectations and 23 for the perceptions) reflecting the five service quality categories tangibles (4 items), reliability (5 items), responsiveness (5 items), assurance (4 items), and empathy (4 items) (5 items). To measure farmers' expectations and perceptions of agriclinic service quality in Puducherry, a 5-point Likert-type scale was adopted, ranging from strongly disagree (1) to strongly agree (5).…”
Section: Methodsmentioning
confidence: 99%
“…Second, few studies have examined the multidimensional brand experiences from the perspective of Chinese customers. In addition, many prior studies have considered brand loyalty as the outcome variable ( Ferreira et al, 2019 ; Quan et al, 2020 ; Khawaja et al, 2021 ), and we investigate the relationship between brand loyalty and repurchase intention based on previous studies. Finally, this study clarifies the relationship between brand attachment and brand loyalty by examining the mediating effect of brand love, which serves as a valuable insight for previous literature which has underestimated the mediation role of brand love.…”
Section: Introductionmentioning
confidence: 99%